Thursday

September 18, 2014

September 18, 2014

Posted by **Erin** on Monday, November 9, 2009 at 9:15pm.

- Algebra -
**Reiny**, Monday, November 9, 2009 at 9:27pmthere is a common factor of 3x

so,

3x^3-12x^2+3x

= 3x(x^2 - 4x + 1)

The last part does not factor any more, so that's it.

**Answer this Question**

**Related Questions**

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

algebra2 - 1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators ...

calc - What is dy/dx of y=12/12X-y^3 ???? Any idea anyone??? y=12/12X-y^3 I ...

Hard algebra qestion - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-...

algebra - 5x -3 = 11 + 12x combine like figures add 3 to both sides to remove ...

Algebra - Can someone please check my work for me. Q: Plot the graph of the ...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

algebra - Andrew factored the expression 20x^3-12x^2+8x as 4x(5x^2-12x^2+8x). ...

Algebra - Andrew factored the expression 20x^3-12x^2+8x as 4x (5x^2-12x^2+8x). ...

algebra - Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6...